ANALISIS FAKTOR PENENTU PROFITABILITAS BANK DI INDONESIA DENGAN METODE RISK BASED BANK RATING (STUDI PADA BANK-BANK UMUM GO PUBLIC di INDONESIA PERIODE 2008-2013) - Krisnawati, Dira Ayu; M Chabachib, M Chabachib (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to analyze the influence of Risk Based Bank Rating to theprofitability of general bank go public listed in the indonesia Stock Exchange. RBBR is the newest assessment that replaced CAMEL from Bank Indonesia, in accordance with Bank Indonesia Circular Letter Number 13/24/DPNP/2011. Factors tested are CAR (Capital Adequacy Ratio), NIM (Net Interest Margin), GCG (Good Corporate Governance), LDR (Loan Deposit Ratio), NPL (Non Performing Loan), and NOP (Net Open Position) towards ROA (Return On Asset).The sample of this study using purposive sampling method, with the number of sample used were 22 general banks go public listed in Indonesian Stock Exchange (IDX) in the periode 2008-2013. Analysis technique used in this study is a multiple linear regression. The result of F test stated that the value of significance is 0,00 means this value indicates that the independent variables impacts the dependent variable significantly. Meanwhile the result of t test showed that NIM has positive and significant effect on the ROA. CAR, LDR, NPL have a negative and significant effect on the ROA. The last is NOP didn’t have a significant effect on the ROA.The result of this analysis showed about 53,2% from the adjusted R2 that ROA can be explained by CAR, NIM, GCG, LDR, NPL, and NOP. The rest 46,8% influenced by other variables outside the model.